Application workload model generation methodologies for system-level design exploration - Saastamoinen, J.; Kreku, J. (2011 Conference on Design and Architectures for Signal and Image Processing, 2011)
As most of the applications of embedded system products are realized in software, the performance estimation of software is crucial for successful system design. Significant part of the functionality of these applications is based on services provided by the underlying software libraries. Often used performance evaluation technique today is the system-level performance simulation of the applications and platforms using abstracted workload and execution platform models. The accuracy of the software performance results is dependent on how closely the application workload model reflects actual software as a whole. This paper presents a methodology which combines compiler based user code workload model generation with workload extraction of pre-compiled libraries, while exploiting an overall approach and execution platform model developed previously. Benefit of the proposed methodology compared to earlier solution is experimented using a set of benchmarks.